The Role of E-Learning in enhancing Total Quality Management in Educational Institutions: an exploratory study of the opinions of a sample of the staff of the Directorate of Education in the province of Nineveh - سليمان, آمال سرحان; شلاش الجبوري, علي جاسم (Journal of Economics and Administrative Sciences, 2020)
Purpose: The research aims to determine the relationship between E-Learning and Total Quality Management (TQM) in Educational institutions in Nineveh Governorates.Methodology / Design: The researchers distributed (30) questionnaires to employees (teachers and administrators) of Nineveh Governorate education who represent the community of the research sample, as they were analyzed using the SPSS V.20The importance of research: The importance of the research in the fact that it focuses on one of the educational methods represented in integrating the traditional method and relying on modern technologies using computers and the Internet in the field of education to improve the reality of education in Iraq in general and the Nineveh Governorate in particular.Theoretical conclusions: This study has reached a number of conclusions, most important of which are that e-learning has many advantages, such as shortening time and effort, providing a diverse learning environment, alternatives and options, encouraging self-education and the possibility of education outside educational institutions without commitment to time and space.Practical results: The results showed a correlation and significant effect between E-learning and total quality management.